Power and privilege in neoliberal perspective: the Laboratory for global performance and politics at Georgetown university. Issue 3 (3rd July 2019) - Majid, Asif
ABSTRACT: The Laboratory for Global Performance and Politics at Georgetown University is an interdisciplinary endeavour operating at the intersection of theatre and international relations. It develops new work; presents global performance; establishes dynamic networks of young and established artists; and cultivates diverse community and financial partnerships. Interviews with Lab staff, archival material, and the author's experience indicate that The Lab functions both as a symbiotic performance-politics relationship that leverages locally voiced performance to enliven global political issues and as a necessary response to a major research institution's neoliberal formations, formations that it seeks to sidestep as much as possible, despite being imbricated within them.